Los procesos de regionalización económica en Asia - María Cristina Rosas (Revista Mexicana de Ciencias Políticas y Sociales)
The appropriateness of providing the pertinent context for the analysis of non-Western cultures ensues from the author's analysis of current regional economic integration processes in Asia, and their specific characteristics, when confronted with the Western concepts on regionalism. Regional integration case studies analyzed include the Pacific Basin countries, the Association of Nations from Southeastern Asia (ANSEA), the Asia-Pacific Economic Forum (APEC), the Cooperation Council of the Gulf (CCG), and the Southern Asia Association for Regional Cooperation (SAARC).